(untitled) (American Journal of Islam and Society, 1989)
Mohammad Taqi Amini is an erudite religious scholar and profound thinker. He possesses an inquisitive mind which refuses to accept things at their face value. He sets out to prove that the reconstruction of Islamic civilization aims at striking a balance between the physical and the spiritual forces inherent in men. He attempts an outline of the scheme of cultural reconstruction. Also, he mentions the effects and implications of Western civilization on modern life and evaluates the impact of two conflicting ideologies. The author believes that for the manifestation of faith and the construction of culture, the necessary good deeds are not mere rituals or outward signs of virtue. Good deeds, on the other hand, comprehend both the inner and outward facets of life and they comprehend the whole being of man. The inner life however, comes first; for without it a healthy community cannot come into existence, nor can man’s use of nature yield any common benefit. The author reveals that in the framework of Western civilization materialism dominates, and materialism recognizes reason as the only source of knowledge. But according to the Islamic concept of cultural reconstruction, the spiritual dimension is the basis of everything and which recognizes the combined guidance of reason, heart and revelation for the acquisition of knowledge. In all spheres of life such a wholesome and all pervasive guidance is needed. The guidance of one faculty is not enough. In Western culture, the essential nature of man is regarded as animalistic and therefore the nature of character is determined in terms of material power and worldly gains. Only those qualities are valuable which have a direct bearing on worldly gains and material power. For example, in business, punctuality, patriotism, social sense, and natural interests are the criteria. On the other hand, qualities which do not have any bearing on worldly gains are not valued. Rather, violation of these qualities is considered a merit. Qualities like modesty, chastity, affection, mutual friendship and love, caring for the family, generosity of heart, soft-heartedness, sincerity, humanity, and consideration for the rights of others have no value for a Western mind. The Islamic scheme of cultural reconstruction, on the other hand, is based on a Divine view of life. This view divides life into material and nonmaterial and insists that both are necessary for the perfection of humanity ...